CAR-T Cell Therapy: A Revolutionary Approach to Targeting and Treating Cancer - Kumar, Virender; Kumar, Davinder; Verma, Monika; Pruthi, Hardik; Dhiman, Tanya; Khatri, Naveen; Garg, Vandana; Kakkar, Saloni; Kumar, Ashwani (Clinical Cancer Drugs, 2025)
CAR-T cell therapy has transformed cancer treatment by harnessing genetically engineered T cells to specifically target and destroy cancer cells, especially in blood cancers like leukemia and lymphoma. Despite its success, challenges such as serious side effect cytokine release syndrome, neurotoxicity and the high cost of treatment hinder widespread access. Research is ongoing to broaden its use to solid tumors and improve its safety, effectiveness, and affordability. Future efforts will focus on refining CAR constructs, reducing adverse effects, enhancing manufacturing efficiency, and ensuring equitable access through regulatory cooperation, facilitating its wider adoption in precision oncology.
Keywords: cancer treatment